Effects of Fertilizers on Growth, Yield and Curcuminoid Content of Turmeric (Curcuma longa L.) Cultivated in Red Clay Loam and Sandy Loam Soil - Baka, Anasrul; Poonpakdee, Chakkrit; Khawmee , Khwunta; Onthong, Jumpen (Burapha Science Journal, 2026)
Soils and fertilizers are important factors affecting growth, yield and quality of turmeric. The influence of chemical fertilizers and cow manure was evaluated on growth, yield and curcuminoid of turmeric cultivated in Suratthani and Rattaphum red clay loam soil and Phatthalung sandy loam soil under different fertilizers. Turmeric without fertilizer cultivated in red clay loam soil displayed higher yield and curcuminoid compared with sandy loam soil.Growth, yield and curcuminoid of turmeric increased when fertilizer was applied, application of chemical fertilizers combined with cow manure grown in red clay loam soil produced highest dry weight (55.42g) and curcuminoid (10.52%) close to application of cow manure at high rate (8 tons/rai) cultivated in Suratthani red clay loam soil. Moreover, cow manure improved physical and chemical properties of soil. Therefore, high rate of cow manure can be used as a source of plant nutrients for turmeric cultivation.